2016
DOI: 10.1007/s11307-016-0956-7
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Wide-Field Fluorescence Endoscopic Device for Molecular Imaging Demonstrating Cathepsin Protease Activity in Colon Cancer

Abstract: Purpose Early and effective detection of cancers of the gastrointestinal tract will require novel molecular probes and advances in instrumentation that can reveal functional changes in dysplastic and malignant tissues. Here, we describe adaptation of a wide-field clinical fiberscope to perform wide-field fluorescence imaging while preserving its white-light capability for the purpose of providing wide-field fluorescence imaging capability to point-of-care microscopes. Procedures We developed and used a fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Cuneo et al found that the same probe could differentiate normal and tumor tissues following radiation therapy in mice and canines [ 148 ]. Further similar clinical applied probes include cathepsin/MMP-sensitive poly-lysine-based near-infrared fluorescence (NIRF) probes [ 149 , 150 ] for the early and effective detection of cancers of the gastrointestinal tract [ 151 ] and pan-cathepsin-sensitive PEG-based probe for the detection of STS and breast cancer [ 129 , 152 ].…”
Section: Hurdle 3: Intracellular Release Of Active Agentmentioning
confidence: 99%
“…Cuneo et al found that the same probe could differentiate normal and tumor tissues following radiation therapy in mice and canines [ 148 ]. Further similar clinical applied probes include cathepsin/MMP-sensitive poly-lysine-based near-infrared fluorescence (NIRF) probes [ 149 , 150 ] for the early and effective detection of cancers of the gastrointestinal tract [ 151 ] and pan-cathepsin-sensitive PEG-based probe for the detection of STS and breast cancer [ 129 , 152 ].…”
Section: Hurdle 3: Intracellular Release Of Active Agentmentioning
confidence: 99%
“…The emitted light has been collected by means of an intensified CCD camera, connected to the image beam of an endoscope. Optical imaging devices using endoscopic pathways and allowing the measurement of the autofluorescence of some endogenous porphyrins have been also proposed for urology, gynecology, and otorhinolaryngology [ 98 , 99 , 100 ]. More recently, two low energy photon excitation technology has been developed, in replacement of the conventional single high energy photon excitation one, making the dye photoexcitation less-harmful and deep-penetrating, even carried out outside the body [ 101 ].…”
Section: Optical Imaging Probesmentioning
confidence: 99%
“…1). Because these proteases are overexpressed by tumor-associated macrophages (TAM) that infiltrate the colorectal tumor microenvironment, their activity is an ideal biomarker for cancer as well as various types of pathogenic inflammation (14,15). Here we demonstrate that 6QC-ICG is an effective contrast agent that enables endoscopic detection of adenomas with high signal-to-background ratios in small animal models, a human-scale spontaneous large animal model, and in a mouse model of inflammation-induced colorectal carcinogenesis.…”
Section: Significancementioning
confidence: 99%